DNA origami nanostructures can exhibit preferential renal uptake and alleviate acute kidney injury. (November 2018) - Jiang, Dawei; Ge, Zhilei; Im, Hyung-Jun; England, Christopher; Ni, Dalong; Hou, Junjun; Zhang, Luhao; Kutyreff, Christopher; Yan, Yongjun; Liu, Yan; Cho, Steve; Engle, Jonathan; et al.
Abstract Patients with acute kidney injury (AKI) frequently require kidney transplantation and supportive therapies, such as rehydration and dialysis. Here, we show that radiolabelled DNA origami nanostructures (DONs) with rectangular, triangular and tubular shapes accumulate preferentially in the kidneys of healthy mice and mice with rhabdomyolysis-induced AKI, and that rectangular DONs have renal-protective properties, with efficacy similar to the antioxidantN -acetylcysteine—a clinically used drug that ameliorates contrast-induced AKI and protects kidney function from nephrotoxic agents. We evaluated the biodistribution of DONs non-invasively via positron emission tomography, and the efficacy of rectangular DONs in the treatment of AKI via dynamic positron emission tomography imaging with68 Ga-EDTA, blood tests and kidney tissue staining. DNA-based nanostructures could become a source of therapeutic agents for the treatment of AKI and other renal diseases. DNA origami nanostructures with different shapes can accumulate preferentially in the kidney, with some being renal-protective, as shown in healthy mice and in a mouse model of acute kidney injury.